The economics of over-the-counter markets: A toolkit for the analysis of decentralized exchange - Hugonnier, Julien; Lester, Benjamin (Princeton Princeton University Press, 2025)
The Economics of Over-the-Counter Markets proposes a unified search-theoretic framework designed to explicitly capture the key features of OTC markets, confront the growing set of stylized facts from these markets, and provide guidance for policies designed to promote liquidity and resiliency. This incisive book covers empirical regularities that are common across OTC markets, develops the methodological tools to analyze the benchmark theoretical models in the academic literature, and extends these models to confront the latest issues facing these markets.